A conceptual Framework for sustainability in Islamic architecture: the significance of the concepts of man and the environment - Omer, Spahic (University of Management and Technology, 2015)
In this paper, I have identified and briefly examined two Islamic concepts which constitute the nucleus of the conceptual framework for sustainability in Islamic architecture. The two concepts are: 1) man as the vicegerent (khalifah) on earth, and 2) the natural environment as both a field and means for man’s vicegerency mission. Central to the paper are the following themes: 1) the meaning and significance of Islamic architecture; 2) the position and role of man on earth; 3) peaceful and accountable (sustainable) coexistence with the environment; and 4) the implications of the Islamic concepts of man and the environment or sustainability in Islamic architecture. The paper aims to increase awareness, both of the professionals and general public, as to the importance of the theme of sustainability in Islamic architecture by expounding the core of the conceptual basis for the same. The paper presents some general principles and ideas around which a comprehensive theory on sustainability in Islamic architecture, in line with the requirements of the Islamic worldview while fully conforming to the dictates of different circumstances, environments and cultures, can be developed today. The nature of the paper: its content, methodology and conclusions, is a conceptual and philosophical rather than an empirical one. The paper concludes that Islamic architecture, through its multidimensionality embodies the message of Islam. It both facilitates the Muslims’ realization of the Islamic purpose and its divine principles on earth and promotes a lifestyle generated by such a philosophy and principles. At the core of Islamic architecture lies function with all of its dimensions: corporeal, cerebral and spiritual. The role of the form is an important one too, but only inasmuch as it supplements and enhances function. Indeed, one of the most recognizable features of Islamic architecture must always be sustainability.